2015
DOI: 10.1007/s00264-014-2644-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of implant design on blood metal ion concentrations in metal-on-metal total hip replacement patients

Abstract: Implant design was the most important factor affecting blood metal ion concentrations. We recommend the regularity of follow-up be tailored to survival rates of various MoM THR designs rather than according to femoral head size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, the small number of cases prevented us from making conclusive observations. Indeed, implant design [18] and small femoral head size [19] have been shown to be significantly associated with increased metal ion concentrations in patients undergoing MoM total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…However, the small number of cases prevented us from making conclusive observations. Indeed, implant design [18] and small femoral head size [19] have been shown to be significantly associated with increased metal ion concentrations in patients undergoing MoM total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical assessment (history, examination, anteroposterior pelvic radiographs, and Oxford Hip Score questionnaire 23 ), all symptomatic patients underwent blood metal ion sampling and cross-sectional imaging. All asymptomatic patients who underwent total hip replacement and asymptomatic patients with BHR implants who had adverse reactions to metal debris risk factors (small femoral components, malpositioned acetabular components, radiographic evidence suggesting implant failure) underwent clinical assessment with blood metal ions 22,24,25 . In line with MHRA guidance, all asymptomatic patients with blood cobalt and/or chromium ion levels of >7 mg/L (the MHRA upper limit) underwent cross-sectional imaging 5 .…”
Section: Follow-upmentioning
confidence: 99%
“…The metal ion data presented are unlikely to be normally distributed, but the authors provide the mean and range for cobalt and chromium. Previous studies have shown blood metal ion distributions to be nonparametric due to the presence of extreme outliers; therefore, the median and interquartile range are preferable when describing these data [7,12]. The variation in mean blood cobalt and chromium reported between the tissue grades may be explained by a few extreme outliers.…”
Section: Resultsmentioning
confidence: 99%
“…It is acknowledged that Fehring et al have detailed the implant designs, and the earlier report clearly excluded patients with bilateral MoM hip bearings. However, given that blood metal ion levels are affected by MoM implant design and modularity [7,8], it would have been preferable to exclude the seven patients with different designs and focus on the 82 patients with DePuy ASR hips.…”
Section: Methodsmentioning
confidence: 99%